6 - A Tribute to ABDALLA BUJRA - Peter Anyang’ Nyong’o (CODESRIA Bulletin, 2025)
The loss of Abdalla Bujra has been easy to accept. His exuberance. His snap questions so sharp. His quiet sense of humour that was always followed by an infectious laugh. Though we had crossed paths at the University of Nairobi in 1970, I got to know Abdalla much better in Dakar in 1975. I had gone to the UN Institute for Development and Economic Planning (IDEP) as a research fellow. My thesis was a study of the ‘Political economy of coPee production in Ivory Coast’. Samir Amin was the director of IDEP then and had done extensive research on agrarian issues in West Africa. He had also published the book L’Afrique de l’Ouest bloquee (translated as Neo-colonialism in West Africa’). I intended to learn from him during my stay at IDEP, which I did. In the meantime, I met Abdalla and Thandika Mkandawire, who were nursing the birth of the Council for the Development of Social Science Research in Africa (CODESRIA) literally ‘on the ribs of IDEP’! I say so because their oPices were tucked somewhere downstairs to the left of the IDEP building, literally ‘struggling to be noticed’. Since both Abdalla and Thandi- ka were immersed in research on agrarian issues, I found their company indispensable. They were both very helpful to me in the work I was doing, especially on the problematic that I had framed in terms of the ‘articulation of modes of production’.